Penggunaan Media Baru dan Perubahan Perilaku dalam Komunikasi Guru dan Siswa di Masa Pembelajaran Jarak Jauh - Hotmaida Marttianno Nainggolan (Metakom, 2022)
Communication between teachers and students from the beginning was done directly and face to face in the classroom. However, when the COVID-19 pandemic hit, learning moved to virtual spaces using various digital media that could be reached by teachers and students at great distances. The development of communication technology and the convergence of mass media make the transition from the old face-to-face way of learning to using various kinds of gadgets. Communication theory in this research is Computer Mediated Computer (CMC). This type of research is qualitative and case study method. Data were obtained through full participant observation and in-depth interviews with informants, then the data were analyzed using descriptive analysis with data validation using Analysis Interactive. The results of the observations showed that there was a change in communication between teachers and students as well as an indication of deviations from the norms of politeness from the participants. In addition, the results of interview revealed that there was an obstacle experienced during PJJ using digital media with internet connection. The purpose of this study is to help teachers and students find ways of communicating that are efficient and effective during PJJ without compromising existing norms and to help overcome obstacles that occur during PJJ.